PESANTREN TRADISIONAL DI ERA MODREN - Nur `Azizah; Wedra Aprison (Adisam Publisher, 2024)
This research is motivated by the implementation of education in traditional Islamic boarding schools which have not been touched by modernization in the form of classical learning methods even though the curriculum has changed and methods have developed a lot. The results of this research are that the Tarbiyah Islamiyah Pasia Islamic boarding school has two curricula, namely the Islamic boarding school curriculum and the independent curriculum, and the 2013 curriculum. The implementation of the learning process in the government curriculum uses a student center approach. However, for the Islamic boarding school curriculum, it cannot be implemented using an independent curriculum, especially if it uses a student center approach. At this Islamic boarding school, students are not allowed to bring cell phones and access to the internet is only provided in the laboratory. Meanwhile, the problem that occurs today is teachers who cannot use technology quickly. Then the teacher is not ready to use student center-based learning methods. And also students who do not realize the potential in religious schools are preaching, while not all students are interested in preaching and this Islamic boarding school has not facilitated that.